SPATIAL PLANNING MANAGEMENT AND TECHNICAL REFORM OF POST JOB CREATION POLICIES - Marfungah L.; Safa’at R.; Istislam; Qurbani I.D. (Biotika, 2023)
Indonesia is fully engaged in the acceleration and prolongation of economic growth. Indonesia expects annual economic growth of 6 percent within 5 (five) years. One indicator of the ease of attracting foreign investors to Indonesia is to have rapid access to the investment licensing process. The Omnibus Legislation is used as a facility to promote the provision of investment. This system, the Spatial Planning Rule, affects at least 79 laws and regulations. This paper intends to analyze the Spatial Planning Law's reform through the omnibus law process, which is applied to the law of work development. Normative legal analysis is this type of research. A conceptual approach is a form used. This research shows that Indonesia's spatial planning reforms to encourage investment should, therefore, be introduced with the use of 5 (five) improvements. Simplifying simpler licensing forms has led to a spatial change in the direction of investment.